2022
DOI: 10.1155/2022/2909993
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Law of Joint Deformation for Grouted Mortise‐Tenon Joint

Abstract: This paper analyzes the law of joint deformation of grouted mortise-tenon joint with 1 : 1 prototype test in key working direction types under 38 working conditions of different joint types, tenon lengths, grouting ranges, grouting materials, and loading combinations for the prefabricated metro station. The deformation performance of the joint has also been compared. In addition, finite element models have been built, and the joint deformation stages are discussed. The influences on the law of joint deformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In China, the monolithic bearing-free prestressed concrete continuous rigid-frame bridge is used in railway bridges. Te structure of the grouted mortise-tenon joints used in the prefabricated structure is complicated, and the force applied to them is special, but there was very little research on these joints before [1].…”
Section: General Situation Of the Projectmentioning
confidence: 99%
“…In China, the monolithic bearing-free prestressed concrete continuous rigid-frame bridge is used in railway bridges. Te structure of the grouted mortise-tenon joints used in the prefabricated structure is complicated, and the force applied to them is special, but there was very little research on these joints before [1].…”
Section: General Situation Of the Projectmentioning
confidence: 99%
“…This pure-bending loading method reduces the influence of shear force on the test results. The other is to directly apply the concentrated loads at the joint position (as shown in Figure 2(b)) [28,29]. This loading method has been proven to cause stress concentration at the joint position in practical processes, affecting the stability and accuracy of the test results.…”
Section: Research Strategymentioning
confidence: 99%
“…The research places particular emphasis on aspects such as fast assembly and controllable quality, and its findings, encompassing the design and fabrication of joint specimens, establishment of a shear-slip constitutive model, and proposal of a simplified analytical method, contribute significantly to the growing body of knowledge in this field. Yang's [33] research has found that grouting plays a crucial role in restricting joint deformations, with the type of grouting material having minimal impact on deformation characteristics. The lengths of the tenons and mortises also influence the ultimate bending capacity of joints, with longer tenons and mortises providing better resistance against deformation.…”
Section: Introduction To Performance Research On Prefabricated Buildi...mentioning
confidence: 99%